Ultra-High Strength Geopolymer Concrete from Industrial Waste: Reducing Anhydrous Sodium Silicate and Steel Fiber Effects - Lelly, Marini; Mannan, Mohammad Abdul; Ahmad Kueh, Beng Hong; Abdul Azim, Abdullah; Farid, Abed; Kandaswamy, Gunasekaran (Springer Nature, 2025)
This study investigates the development of ultra-high strength geopolymer concrete (UHSGC) through optimized precursor and activator formulations targeting both mechanical performance and sustainability. Eight mix groups were designed by reducing anhydrous sodium silicate (ASS) and incorporating fly ash, slag, silica fume, and liquid sodium silicate (LSS), with or without steel fiber reinforcement. Mechanical properties, pore structure, permeability, and environmental impacts were assessed following ASTM standards and life cycle assessment metrics. Steel fibers enhanced compressive strength to 172.1 MPa but at significant environmental costs (+ 369% EE, + 223% CO₂, + 158% cost). Silica fume (155.8–163.8 MPa) and slag (up to 168.2 MPa) improved strength with minimal trade-offs, while fly ash, water, and superplasticizer reduced strength (143.2–146.5 MPa). Partial substitution of ASS with LSS improved strength (159.5–166.4 MPa) and porosity, whereas full LSS replacement reached 170.4 MPa with the lowest porosity (9.2%) but moderately higher impacts (+ 16% EE, + 11% CO₂, + 13% cost). These findings demonstrate that slag and partial LSS substitution offer the most efficient balance between performance and sustainability, while full LSS replacement provides superior strength and durability at acceptable environmental trade-offs.